Brand Image, Product Quality, and Price in Skincare Purchase Decisions: Citra Merek, Kualitas Produk, dan Harga Dalam Keputusan Pembelian Produk Perawatan Kulit - Rahmatika , Fizza Ainun Yaumil; Indayani, Lilik (Indonesian Journal of Law and Economics Review, 2025)
General Background: The skincare industry in Indonesia is rapidly expanding, driven by consumer awareness of skin health and appearance. Specific Background: Beauty Glow, a local halal skincare brand, competes within this dynamic market, requiring effective marketing strategies to sustain consumer interest and loyalty. Knowledge Gap: While prior research examined brand image, product quality, and price independently, limited studies have explored their combined role in shaping purchasing decisions for local skincare brands. Aims: This study investigates how brand image, product quality, and price collectively influence consumer purchase decisions for Beauty Glow skincare in Sidoarjo. Results: Using quantitative methods and multiple linear regression analysis with 100 respondents, findings reveal that all three variables—brand image, product quality, and price—significantly and positively correlate with purchasing decisions. Novelty: The study integrates these variables simultaneously to understand their cumulative contribution to consumer behavior in a halal-certified, locally produced skincare context. Implications: The results underscore the importance for local skincare producers to enhance product quality and maintain competitive pricing while strengthening brand perception to increase consumer trust and purchase intentions. Highlights: Examines brand image, product quality, and price simultaneously. Focuses on halal-certified local skincare consumers. Offers strategic insights for enhancing purchase intention. Keywords: Brand Image, Product Quality, Price, Purchasing Decision, Skincare Marketing